A fatal case of JC virus meningitis presenting with hydrocephalus in a human immunodeficiency virus–seronegative patient. Issue 1 (20th June 2014) - Agnihotri, Shruti P.; Wuthrich, Christian; Dang, Xin; Nauen, David; Karimi, Reza; Viscidi, Raphael; Bord, Evelyn; Batson, Stephanie; Troncoso, Juan; Koralnik, Igor J.
<x xml:space="preserve">Abstract</x> JC virus (JCV) is the etiologic agent of progressive multifocal leukoencephalopathy, JCV granule cell neuronopathy, and JCV encephalopathy. Whether JCV can also cause meningitis has not yet been demonstrated. We report a case of aseptic meningitis resulting in symptomatic hydrocephalus in a human immunodeficiency virus–seronegative patient. Brain imaging showed enlargement of ventricles but no parenchymal lesion. She had a very high JC viral load in the cerebrospinal fluid (CSF) and developed progressive cognitive dysfunction despite ventricular drainage. She was diagnosed with pancytopenia and passed away after 5.5 months. Postmortem examination revealed productive JCV infection of leptomeningeal and choroid plexus cells, and limited parenchymal involvement. Sequencing of JCV CSF strain showed an archetype‐like regulatory region. Further studies of the role of JCV in aseptic meningitis and in idiopathic hydrocephalus are warranted. Ann Neurol 2014;76:140–147